Harvest more knowledge - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
If you want to top up your local knowledge, there are herbaria, botanical gardens, research institutes, NGOs and universities with agricultural, biological and medical faculties in your region or country that focus on medicinal plants, their...